2018
DOI: 10.1024/1661-8157/a002940
|View full text |Cite
|
Sign up to set email alerts
|

Der Einfluss von Religiosität und Spiritualität auf die Haltung von Schweizer Ärzten gegenüber ethisch umstrittenen medizinischen Fragen

Abstract: Zusammenfassung. Obwohl das Thema Religiosität und Spiritualität (R/S) in der Medizin immer mehr an Bedeutung gewinnt, wurden die religiösen Haltungen von Ärzten und ihre Auswirkungen auf die ethische Entscheidungsfindung in der Schweiz bisher kaum untersucht. Die vorliegende Studie evaluiert deshalb den Einfluss von R/S auf die Einstellung von Ärzten gegenüber ethisch umstrittenen medizinischen Fragen. Die Resultate zeigen, dass religiöse Ärzte mehr Vorbehalte in Bezug auf ärztlich assistierten Suizid, Schwan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…From within the NERSH collaboration Lee et al were able to share with us a sample of German hospital chaplains (N = 138), [27] and Hefti et al had used the questionnaire to query family practitioners from the region of Bale and Aarau in Switzerland (N = 105). [28] The citation search found 4 eligible surveys. Cordero et al had collected 2 samples of Spanish and Portuguese nursing students,[ 29 30 ] (N = 75 and N = 158 respectively), and from Brazil by Menegatti-Chequini et al we identified 2 samples of psychiatrists: the first based on a survey among members of the Brazilian Psychiatry Association (ABP) (N = 508), and also a sample from a psychiatric department in São Paulo (N = 84).…”
Section: Methodsmentioning
confidence: 99%
“…From within the NERSH collaboration Lee et al were able to share with us a sample of German hospital chaplains (N = 138), [27] and Hefti et al had used the questionnaire to query family practitioners from the region of Bale and Aarau in Switzerland (N = 105). [28] The citation search found 4 eligible surveys. Cordero et al had collected 2 samples of Spanish and Portuguese nursing students,[ 29 30 ] (N = 75 and N = 158 respectively), and from Brazil by Menegatti-Chequini et al we identified 2 samples of psychiatrists: the first based on a survey among members of the Brazilian Psychiatry Association (ABP) (N = 508), and also a sample from a psychiatric department in São Paulo (N = 84).…”
Section: Methodsmentioning
confidence: 99%
“…23 Also, a Swiss data sample of 104 general practitioners from a survey by Hefti et al in 2015 was now available. 24 The Swiss survey was published in German language and would thus not have been found by the citation or literature searches.…”
Section: Systematic Searchesmentioning
confidence: 99%
“…26 The data on German hospital chaplains were collected in a nation-wide survey by Lee et al,23 while the Swiss sample of General practitioners was a random sample from the region of Bale and Aarau by Hefti et al24 From Menegatti-Chequini et al we received two samples, the first based on a survey sent to members of the Brazilian Psychiatry Association (ABP) and an additional sample from a single psychiatric department Instituto de Psiquiatria, Hospital das Clínicas, Faculdade de Medicina, Universidade de São Paulo (IPqHC-FMUSP). Duplicates from the ABP and IPqHC-FMUSP samples were removed.…”
mentioning
confidence: 99%
“…20 Also, a Swiss data sample of 104 general practitioners from a survey by Hefti et al in 2015 was now available. 21 The Swiss survey was published in German language and would thus not have been found by the citation or literature searches.…”
Section: Systematic Searchesmentioning
confidence: 99%
“…were 3 rd -and 4 th -year students from the School of Health of University of Algarve and School of Health of Polytechnic Institute of Santar 23. The data on German hospital chaplains was collected in a nation-wide survey by Lee et al,20 while the Swiss sample of General practitioners were a random sample from the region of Bale and Aarau by Hefti et al21 From Menegatti-Chequini et al we received two samples, the first based on a survey sent to members of the Brazilian Psychiatry Association (ABP) and an additional sample from a single psychiatric department Instituto de Psiquiatria, Hospital das Clínicas, Faculdade de Medicina, Universidade de São Paulo (IPqHC-FMUSP). Duplicates from the ABP and IPqHC-FMUSP samples were removed.…”
mentioning
confidence: 99%